An Advanced Study of Health Status among School Going Adolescents in South India - Pravin N. Yerpude; Keerti S. Jogdand; Mohini Jogdand (Challenges in Disease and Health Research Vol. 5, 2021)
Introduction: In human growth and maturation, adolescence period is significant. In India, 21.4 percent population is adolescents (10-19 years) which accounts for one fifth of the total population. One of the important index of the national investment in the development of its future manpower is the health and nutritional status of the children in the country. For maintaining good health in adult, it is very important to achieve optimum growth during adolescent age. Many of health problems in children can be detected by providing school health services. We can treat and prevent many of serious complications in children through regular school survey. The present study was carried out with the objective to assess health status and morbidity pattern among school going adolescents in urban area of South India. Materials and Methods: The present study was conducted in the year 2010 in 3 urban schools which are in the field practice area of department of community medicine. A team of doctor, social workers and school teachers examined all children in the age group of 10 to 19 Years studying in these schools. Results: In the present study, 210 adolescents participated. Out of them 72(34.29%) were girls and 138 (65.71%) were boys. According to weight for age criteria, 53.33% of the adolescents were found to be normal and 46.67% were malnourished. By applying height for age criteria it was found that 32.86 % of the adolescents were stunted with boys suffering more 66.67% as compared to girls 33.3%. The dental caries was the commonest (41.90%) among all health problems. Conclusion: The study shows that the health and nutritional status among the adolescents was low. Under nutrition is common public health problem worldwide mostly in developing countries including India. Proper nutrition is required for adequate growth and development of the child. A periodical and regular health check-up with concerted efforts towards nutrition of adolescents along with focused health education will improve the health and nutritional status of these schools going adolescents in their future.